A new small, mesorostrine inioid (Cetacea, Odontoceti, Delphinida) from four upper Miocene localities in the Pisco Basin, Peru. (25th July 2020) - Lambert, Olivier; Collareta, Alberto; Benites‐Palomino, Aldo; Di Celma, Claudio; de Muizon, Christian; Urbina, Mario; Bianucci, Giovanni
Abstract: The moderately rich past diversity of the superfamily Inioidea (Cetacea, Odontoceti) in both the Atlantic and Pacific oceans contrasts with the present survival of a single genus ( Inia, Amazon river dolphin, family Iniidae) in freshwater deposits of South America and of a single species ( Pontoporia blainvillei, franciscana, family Pontoporiidae) along the eastern coast of that continent. However, part of the late Miocene – Pliocene inioid fossil record consists of relatively fragmentarily known species, for which systematic affinities remain poorly understood. Based on a sample of six cranial specimens from lower upper Miocene (Tortonian, 9.5–8.6 Ma) marine deposits of the Pisco Formation exposed at four localities of the East Pisco Basin (southern coast of Peru), we describe a new genus and species of inioid, Samaydelphis chacaltanae . This mesorostrine, small‐sized species is characterized by an upper tooth count of c. 30 teeth per row, a moderately elevated vertex of the cranium displaying a long anteromedial projection of the frontals and interparietal, and the plesiomorphic retention of a premaxilla–nasal contact. Recovered as a member of the family Pontoporiidae in our phylogenetic analysis, S. chacaltanae falls as sister group to Meherrinia isoni, from the upper Miocene of North Carolina (USA), which has previously been tentatively referred to the Iniidae or regarded as a stem Inioidea. Originating from the P1 allomember of the Pisco Formation, the mesorostrine S. chacaltanae was contemporaneous and sympatric with two other inioids, the brevirostrine pontoporiid Brachydelphis mazeasi and the longirostrine iniid Brujadelphis ankylorostris .